Using evidence-based applied positive psychology to promote student well-being - Fält-Weckman, Stefania; Fagerlund, Åse; Londen, Monica; Lagerström, Martin (Frontiers in Psychology, 2024)
There has been a noticeable decline in life satisfaction among adolescents globally in recent years. The present study explored the immediate and long-term effects of a positive psychology intervention course, Study with Strength, on the well-being of students at general upper secondary school in Finland during the pandemic. Based on a partly randomized wait-list control group design, the study included a final sample of 350 students from 10 schools. Self-report measures were used to assess both immediate between-group effects and long-term within-group effects of the intervention on student well-and ill-being. A combination of methods from positive psychology and cognitive therapy were applied, and the course was administered by the participating schools' own teachers and student-welfare personnel. The findings show that the Study with Strength intervention course enhanced the students' experiences of positive practices at school, happiness and of positive emotions. However, the effect sizes were small. The intervention did not have any immediate effects on all aspects of well-being, negative emotions, depression, or study-related burnout. There were significant changes in students' well-being in the analysis of long-term effects. The students also reported a positive effect of the intervention both on their personal lives and in their studies. Overall, it appears that the intervention had a small but positive impact, nudging students towards enhanced well-being. The results offer valuable insights into the implementation of positive education on students at general upper secondary school aged 15-19.